Photocatalytic removal of 2,4,6-trichlorophenol from water exploiting commercial ZnO powder. - Gaya, Umar Ibrahim; Abdullah, Abdul Halim; Hussein, Mohd. Zobir; Zainal, Zulkarnain (Elsevier, 2010)
2,4,6-trichlorophenol is an important water pollutant owing to the severity of its toxicity. The aqueous phase photocatalytic oxidation of 2,4,6-trichlorophenol over ZnO was investigated as a potential method for the abatement of this pollutant. The effects of operating parameters such as initial ZnO doses and substrate concentration on the removal of 2,4,6-trichlorophenol were studied and optimised at 0.75 g L− 1 and 50 mg L− 1, respectively. The photocatalytic system afforded the highest degradation efficiency at neutral pH. The decomposition of 2,4,6-trichlorophenol by the photoprocess agreed satisfactorily with pseudo zero-order kinetic model. The effect of the presence of SO42−, S2O82−, HPO42− and Cl− on the 2,4,6-trichlorophenol removal rate was for the first time revealed. Some hitherto unreported pathway intermediates of ZnO-assisted 2,4,6-trichlorophenol degradation were recorded using gas chromatography–mass spectrometry (GC–MS) and high performance liquid chromatography (HPLC). A tentative reaction mechanism for the formation of these intermediates was proposed.